Cervical cancer. Clinicopathological data. Early diagnosis, developmental stages - Zuckermann, Conrado (2015)
Synthetically we present the facts we consider presently useful and generally accepted. In this regard we note that the literature is extremely large, opinions sometimes diverge and that precisely in this connection carried out frequently, round tables and symposia that try to unify criteria.